Efficiency based modulation for wheelchair driving collaborative control. - Urdiales-García, Amalia Cristina; Fernández-Carmona, Manuel; Peula Palacios, José Manuel; Annicchiaricco, Roberta; Sandoval-Hernández, Francisco; Caltagirone, Carlo (IEEE, 2010)
This work presents a new approach to shared control to assist wheelchair driving. Rather than swapping control from human to robot either by request or on a need basis, the system estimates how much help is needed in a reactive fashion and continuously produces an emergent motory command in combination with human input. To provide time stability and integration, instant commands are modulated by a factor depending on human efficiency in a shifting time window. Thus, the better the person drives, the more control he/she is awarded with. The approach has been tested at Fondazione Santa Lucia (FSL) in Rome with volunteers presenting different disabilities. All volunteers managed to finish a mildly complicated trajectory with door crossing and major turns and the proposed system increased efficiency in all cases.
https://conferences.ieeeauthorcenter.ieee.org/author-ethics/guidelines-and-policies/post-publication-policies/
Keywords: Robótica; Ergonomía; Sillas de ruedas; Shared control; Robotic wheelchair; Assistive robotics